Direct evidence for the occurrence of superconductivity in the magnetic compound YFe₄Al₈ - Rybaltchenko, L.F.; Wyder, P.; Jansen, A.G.M.; Dmitriev, V.M.; Prentslau, N.N.; Suski, W. (Физика низких температур, 2002)
For the first time we present the direct evidence for superconductivity in the ternary magnetic compound YFe₄Al₈ with the ThMn₁₂ type structure found via point-contact (PC) experiments on contacts between silver needle and single-crystal YFe₄Al₈, revealing the distinct Andreev-reflection current. The spectra measured prove the existence of normal-superconducting interface and exhibit the triangular-like shape in a vicinity of zero-bias voltage, inferring the unconventional type of superconductivity. The derived dependences of the order parameter versus temperature Δ(T) and m agnetic field Δ(H) are presented. Δ(T) follows BCS theory, whereas Δ(H) do not satisfy any theoretical predictions. In some cases there exists noticeable superconductivity enhancement by a weak magnetic field. The data obtained imply the v ery inhomogeneous distribution of superconductivity over the sample volume in spite of its single crystal structure. We assume that the reason is associated with inherent magnetic inhomogeneities of this material. The highest values for the critical temperature Tc, upper critical magnetic field Hc₂, and ratio 2Δ(0)/kTc are 7.4 K, 5 T, and 7.2, respectively.